A rare case of Mayer-Rokitansky Küster-Hauser syndrome with ectopic kidney - Shil, Kishore K.; Mahrukh, Hafsa; Ferdousi, Tahmina; Banu, Hurjahan; Sultana, Nusrat; Hasanat, Muhammad A. (International Journal of Research in Medical Sciences, 2024)
Mayer-Rokitansky Küster-Hauser (MRKH) syndrome is a congenital anomaly of female reproductive system and is the second most common cause of primary amenorrhea. Utero-vaginal agenesis also may be associated with different other congenital anomalies and mostly involve the renal and skeletal system. Karyotyping and gonadal development are normal. So, patient’s anthropometric measurement, secondary sexual characteristics and hormonal profile are usually normal. Transabdominal sonography and MRI can confirm the absence of uterus, cervix and upper part of vagina, as well as can identify another associated congenital anomaly. We report the case of 25-year-old women presented with primary amenorrhea and normally developed secondary sexual characteristics with normal external genitalia. Transabdominal sonography and MRI revealed agenesis of uterus, normal ovary and ectopic right kidney. MRKH syndrome with ectopic kidney is a rare form of mullerian agenesis.